Remote Wiping and Secure Deletion on Mobile Devices: A Review. Issue 6 (21st September 2016) - Leom, Ming Di; Choo, Kim‐Kwang Raymond; Hunt, Ray
Abstract: Mobile devices have become ubiquitous in almost every sector of both private and commercial endeavors. As a result of such widespread use in everyday life, many users knowingly and unknowingly save significant amounts of personal and/or commercial data on these mobile devices. Thus, loss of mobile devices through accident or theft can expose users—and their businesses—to significant personal and corporate cost. To mitigate this data leakage issue, remote wiping features have been introduced to modern mobile devices. Given the destructive nature of such a feature, however, it may be subject to criminal exploitation (e.g., a criminal exploiting one or more vulnerabilities to issue a remote wiping command to the victim's device). To obtain a better understanding of remote wiping, we survey the literature, focusing on existing approaches to secure flash storage deletion and provide a critical analysis and comparison of a variety of published research in this area. In support of our analysis, we further provide prototype experimental results for three Android devices, thus providing both a theoretical and applied focus to this article as well as providing directions for further research.